Efficacy of overactive neurogenic bladder treatment: A systematic review of randomized controlled trials - Rawa Bapir; Kamran Hassan Bhatti; Ahmed Eliwa; Herney Andrés García-Perdomo; Nazim Gherabi; Derek Hennessey; Vittorio Magri; Panagiotis Mourmouris; Adama Ouattara; Gianpaolo Perletti; Joseph Philipraj; Konstantinos Stamatiou; et al. (Archivio Italiano di Urologia e Andrologia, 2022)
Background: Overactive bladder (OAB) symptoms of frequency, urgency and urge incontinence are frequently associated with known neurological diseases like multiple sclerosis (MS), spinal cord injury (SCI), Parkinson’s disease (PD), stroke. Objective: The aim of our study was to review the efficacy of pharmacological and non-pharmacological treatments for neurogenic overactive bladder. Materials and methods: We searched two electronic databases (PubMed and EMBASE) for randomized controlled trials focusing on pharmacological and non-pharmacological medical treatments for overactive bladder symptoms associated with neurological diseases published up to 30 April 2022. Results: A total of 157 articles were retrieved; 94 were selected by title and abstract screening; after removal of 17 duplicates, 77 records were evaluated by full-text examination. Sixty-two studies were finally selected. The articles selected for review focused on the following interventions: anticholinergics (n = 9), mirabegron (n = 5), comparison of different drugs (n = 3), cannabinoids (n = 2), intravesical instillations (n = 3), botulinum toxin (n = 16), transcutaneous tibial nerve stimulation (TTNS) (n = 6), acupuncture (n = 2), transcutaneous electrical nerve stimulation TENS (n = 4), pelvic floor muscle training (PFMT) (n = 10), others (n = 2). Anticholinergics were more effective than placebo in decreasing the number of daily voids in patients with PD (mean difference [MD]- 1.16, 95 % CI - 1.80 to - 0.52, 2 trials, 86 patients, p < 0.004), but no significant difference from baseline was found for incontinence episodes and nocturia. Mirabegron was more effective than placebo in increasing the cystometric capacity in patients with MS (mean difference [MD] 89.89 mL, 95 % CI 29.76 to 150.01, 2 trials, 98 patients, p < 0.003) but no significant difference was observed for symptom scores and bladder diary parameters. TTNS was more effective than its sham-control in decreasing the number of nocturia episodes (MD -1.40, 95 % CI -2.39 to -0.42, 2 trials, 53 patients, p < 0.005) but no significant changes of OAB symptom scores were reported. PFMT was more effective than conservative advice in decreasing the ICIQ symptom score (MD, -1.12, 95 % CI -2.13 to -0.11, 2 trials, 91 patients, p = 0.03), although the number of incontinence episodes was not significantly different between groups. Conclusions: The results of the meta-analysis demonstrate a moderate efficacy of all considered treatments without proving the superiority of one therapy over the others. Combination treatment using different pharmacological and non-pharmacological therapies could achieve the best clinical efficacy due to the favorable combination of the different mechanisms of action. This could be associated with fewer side effects due to drug dosage reduction. These data are only provisional and should be considered with caution, due to the few studies included in metaanalysis and to the small number of patients.